Preparation And Characterization Of LSCF-CuO Using Solid State Method As Cathode Material For Intermediate Temperature Solid Oxide Fuel Cell (IT-SOFC) - Abd Razak, Muhammad Nur Ramadhan (Universiti Sains Malaysia, 2018)
Solid oxide fuel cells (SOFC) is one of the most widely used groups of fuel cell in engineering products which converts the chemical energy directly to electrical energy and thermal energy by using electrochemical reactions. IT-SOFC is a type of fuel cell which is operated at intermediate temperature between 600 – 800ºC give a better electrochemical performance and reduce the material and operating cost. LaSrCoFeO3 (LSCF) is a perovskite cathode material commonly used in intermediate temperature solid oxide fuel cell (IT-SOFC) which give the better electrochemical performance as compared with the classical SOFC. This research investigated the chemical, physical and electrochemical characteristic of LSCF composite with CuO which synthesized by conventional solid-state method. The calcined powders were analyzed by X-ray diffraction analysis (XRD), scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDX), thermogravimetric analysis (TGA) and Brunauer- Emmett- Teller analysis (BET). XRD data showed the single-phase perovskite LSCF-CuO at temperature 700ºC. SEM images showed the LSCF-CuO particle size increased as the calcination temperature increased. The BET showed the specific surface area and total pores volume decreased as the calcination temperature increased. The lowest polarization resistance (Rp) value for LSCF-CuO cathode was 0.41 Ω.cm2 at temperature 800ºC.